2020
DOI: 10.1002/brb3.1592
|View full text |Cite
|
Sign up to set email alerts
|

Activation of brain‐derived neurotrophic factor signaling in the basal forebrain reverses acute sleep deprivation‐induced fear memory impairments

Abstract: Introduction:The mechanisms underlying sleep deprivation-induced memory impairments and relevant compensatory signaling pathways remain elusive. We tested the hypothesis that increased brain-derived neurotrophic factor (BDNF) expression in the basal forebrain following acute sleep deprivation was a compensatory mechanism to maintain fear memory performance. Methods: Adult male Wistar rats were deprived of 6-hr total sleep from the beginning of the light cycle. The effects of sleep deprivation on BDNF protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Studies have shown that SD can disrupt memory consolidation via altering the hippocampal expression of genes related to synaptic plasticity and memory such as BDNF (Karabulut et al, 2019). BDNF expression is associated with the sleep debt of rats (Ma et al, 2020). It has been shown that 24 hours of RSD reduces BDNF and TrkB levels in the hippocampus and disrupts spatial memory performance of rats in the Morris water maze apparatus (Mahboubi et al, 2019).…”
Section: The Effect Of Tsd On Memory Performance and Gene Expressionmentioning
confidence: 99%
“…Studies have shown that SD can disrupt memory consolidation via altering the hippocampal expression of genes related to synaptic plasticity and memory such as BDNF (Karabulut et al, 2019). BDNF expression is associated with the sleep debt of rats (Ma et al, 2020). It has been shown that 24 hours of RSD reduces BDNF and TrkB levels in the hippocampus and disrupts spatial memory performance of rats in the Morris water maze apparatus (Mahboubi et al, 2019).…”
Section: The Effect Of Tsd On Memory Performance and Gene Expressionmentioning
confidence: 99%
“…Rapid eye movement (REM) sleep disturbances can relieve symptoms of depression or cause mania. At the same time, after REM sleep deprivation, there is a sudden and short elevation in the BDNF level [ 129 , 130 , 151 , 152 , 153 ].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests a need for more intricately designed studies, whereby brain regions of interest are temporarily deactivated during a selected memory maintenance time-frame (e.g., for a 2 week period following CFC, but not during the memory recall period). Another potential experiment that could assess the functional role of these markers in fear maintenance would be to administer ANA-12, an antagonist for the BDNF receptor TrKB (Ma et al, 2020 ). If microinjection of ANA-12 into the pre-limbic cortex altered the maintenance of fear memory, then a functional role for BDNF could be confirmed.…”
Section: Discussionmentioning
confidence: 99%